PERAN DINAS PENGELOLAAN PASAR DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH DI DAERAH KOTA SAMARINDA. - Heriansyah Heriansyah (Universitas 17 Agustus 1945 Samarinda, 2013)
ABSTRACTIONHeriansyah, Fakultashukum, University 17 August 1945, Samarinda Kalimantan East. Evaluation Evaluation Punish Role On Duty Management Of Market In Improving Original Opinion In Area Town of Samarinda .In guiding by DrawanHasyim, SH, M.Hum and of Elviyanti Double of Mas, SH, M.Hum.Target of this penelituan is to know the Target of Deskirptif and Creative Target. To know execution of purchasing and selling agreement of kiosk / los,untuk know the way of switchover of rights and way of payment in purchasing and selling agreement of kiosk / kiosk [in] market of Segiriulusamarinda . To know do purchasing and selling agreement have fully to regulation arranging about sales in general.Pursuant to solution of Execution of purchasing and selling agreement of kiosk / kiosk [in] market of segiriSamarinda, arranged in by law of number 5 year 2010 about containing market retribution about obligation of merchant that is paying retribution and [his/its] rights to get merchant bill of evidence showing type, location and situation, dasaranto trade.